Writing time : studies in serial literature, 1780-1850 - Franzel, Sean (Cornell University Press and Cornell University Library, 2023)
"This book is a study of time and seriality in the nineteenth-century periodical."-- Provided by publisher.
"A Signale Book."
Keywords: Time in literature.; Time -- Philosophy -- History -- 19th century.; Serial publications -- Europe -- History -- 19th century.; Authors and readers -- History -- 19th century.; Écrivains et lecteurs -- Histoire -- 19e siècle.; Temps -- Philosophie -- Histoire -- 19e siècle.; Temps dans la littérature.; Publications en série -- Europe -- Histoire -- 19e siècle.; LITERARY CRITICISM / Books & Reading.; Authors and readers; Serial publications; Time in literature; Time -- Philosophy; Europe; Germany.; Literature: history & criticism.; Museology & heritage studies.; Historiography.; Media Studies.; 1800-1899; Zeitgeschichte, nineteenth century cultural journalism, periodical studies, Koselleck, techniques of temporalization, history of the present, German-language authors.; Electronic books.; History